COVID-19 knowledge, attitude, practices, and associated factors among Bangladeshi food handlers from various food industries - Md Fahad Jubayer; Md Shahidullah Kayshar; Md Faizul Kabir; Md Shoaib Arifin; Md Amirul Islam; Md Mizanur Rahman; Md Tariqul Islam Limon; Aney Parven; Islam Md Meftaul (Elsevier, 2023)
Background and objectives: It is believed that preventive safety measures are the most effective way to avoid the COVID-19. The adherence of workers to these measures is largely determined by their knowledge, attitude, and practices (KAP). Because they are in close proximity to consumable items, workers in the food industry must be especially vigilant during this period. The purpose of this present study was to evaluate the COVID-19 knowledge, attitudes, and practices of food handlers in different food industries of Bangladesh. Study design: This was a cross-sectional study. Methods: This included the participation of 400 food handlers from 15 food industries. The information was collected from the participants through a questionnaire prepared in Google form. Different nonparametric tests and a linear regression model were performed for statistical analysis. Results: With a correct response rate of about 90% on average (knowledge 89.7%, attitude 93%, practices 88.2%), the participants showed an acceptable KAP (>80% correct response) regarding COVID-19. Education (p = 0.00) and working experiences (p = 0.01) had a significant association with the total KAP scores. Conclusion: Food handlers in the food industries of Bangladesh have adequate knowledge, a positive attitude, and the desired practices regarding the COVID-19 issue.